A boundary integral method for the three-dimensional heat equation subject to speci'cation of energy - Ang, W.T.; Gumel, A.B. (Elsevier Science B.V., 2001)
A boundary integral method is proposed for the numerical solution of the three-dimensional heat equation subject to speci'cation of energy. A speci'c test problem is solved using the method. c 2001 Elsevier Science B.V. All rights reserved.